2020
DOI: 10.11604/pamj.2020.36.100.23892
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean delivery of first prediagnosed COVID-19 pregnancy in Nigeria

Abstract: The COVID-19 pandemic is currently causing widespread infection and deaths around the world. Since the identification of the first case in Nigeria in February 2020, the number of confirmed cases has risen to over 9,800. Although pregnant women are not necessarily more susceptible to infection by the virus, changes to their immune system in pregnancy may be associated with more severe symptoms. Adverse maternal and perinatal outcomes have been reported among pregnant women with COVID-19 infection. However, lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The characteristics of included trials were presented in Table 1 . A total of 269 patients from 47 studies [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] were included in our meta-analysis. The mean age of operative patients with COVID-19 was 50.91 [95% CI, 42.49; 59.34], and 49% [95% CI, 0.33, 0.65] patients were female.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of included trials were presented in Table 1 . A total of 269 patients from 47 studies [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] were included in our meta-analysis. The mean age of operative patients with COVID-19 was 50.91 [95% CI, 42.49; 59.34], and 49% [95% CI, 0.33, 0.65] patients were female.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 47 studies included in the analysis, only 20 studies [ 16 , [18] , [19] , [20] , 24 , 25 , 29 , 32 , 39 , 42 , 45 , 46 , 50 , 53 , [55] , [56] , [57] , [58] , [59] , 61 ] reported the information of medical staff infection which identified that a total of 38 medical staff were infected, and medical staff who used biosafety level 3 (BSL-3) protective equipment during the perioperative period did not get infected.…”
Section: Resultsmentioning
confidence: 99%
“…LUTH managed the first pregnant woman with confirmed COVID-19 in Nigeria. The hospital subsequently put together a multidisciplinary team of obstetricians, anaesthetists, neonatologists, nurses, psychiatrists and infectious disease control experts to provide care for these women (Ishola, 2020; Makwe et al ., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] However, although pregnant women are not necessarily more susceptible to infection by the virus, changes to their immune system in pregnancy may be associated with more severe symptoms. 8 Adverse maternal and perinatal outcomes have been reported among pregnant women with COVID-19infection, including maternal pneumonia and maternal death, intrauterine fetal death/stillbirth, preterm birth, neonatal pneumonia/sepsis, disseminated intravascular coagulopathy and neonatal death. [9][10][11] Though congenital infection with COVID-19 infection has not been documented, and the virus has not been detected in expelled products of conception, the possibility of vertical transmission exists.…”
Section: Introductionmentioning
confidence: 99%
“…6,9,10 Literature on the antenatal and perinatal management and outcomes of COVID-19infection in pregnancy in Nigeria and sub-Saharan Africa is gradually emerging, but sparse. 8 Clinical characterisation of COVID-19 infection in pregnancy is important for prognostication, health care guidelines and policy formulation. The few studies done in Nigeria, though did not document significant association between COVID-19 infection in pregnancy and adverse maternal and perinatal outcomes, did not compare these outcomes with that of the general pregnant population.…”
Section: Introductionmentioning
confidence: 99%